Mulheres camponesas em movimento: sua organização e resistência no assentamento Fernando Silva em Porangatu- Goiás - Anzilago, Julciane Inês [UNESP] (2014)
The development of agrarian capitalism in Brazil, especially in recent decades, has caused a series of profound changes in the State of Goiás. Agribusiness, with its logic of productivity and profit, has de-territorialized peasants, disrupting established social relations and interfering in the social formation. Favored by public policies, agribusiness concentrates its control over the countryside, forcing small farmers to leave the land, exploiting workers, all with the intention to monopolize the factors of production. In this process, female peasants, who already suffer double duties, working in the fields as well at the home, have experienced worsening conditions, often becoming the only adult available to take responsibility for all the duties needed to support their families. Given these circumstances, their resistance is crucial to preserve peasant productivity and reproduction. The present study has as its main objective contributing to understanding the struggle of peasant women to build their leadership in securing beneficial public policies in the context of contemporary capitalist development in the countryside of Goiás. It analyzes the specific case of peasant settlements in the municipality Porangatu, especially the Fernando Silva Agrarian Reform Settlement, which has been the focus of organizing by the Peasant Women's Movement (Movimento de Mulheres Camponesas - MMC). Women there were interviewed and studied to understand the progress of their struggles through their growing awareness about the challenges of gender relations within their home...